2010
DOI: 10.1016/j.applthermaleng.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the performance of a novel loop heat pipe solar water heating system for use in Beijing, China

Abstract: A novel loop heat pipe (LHP) solar water heating system for typical apartment buildings in Beijing was designed to enable effective collection of solar heat, distance transport, and efficient conversion of solar heat into hot water. Taking consideration of the heat balances occurring in various parts of the loop, such as the solar absorber, heat pipe loop, heat exchanger and storage tank, a computer model was developed to investigate the thermal performance of the system. With the specified system structure, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Wang et al [22] presented a novel kind of micro-heat pipe array flat plate solar water heater with an annual average system efficiency of 58.29%. Use of a novel LHP for solar heat collection and transportation was recently proposed by Zhao et al [23] and still at the research stage. Recent research indicated that LHPs used in the buildings' hot water systems could achieve the enhanced performance if the solar absorber and heat exchanger are adequately selected and coupled [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [22] presented a novel kind of micro-heat pipe array flat plate solar water heater with an annual average system efficiency of 58.29%. Use of a novel LHP for solar heat collection and transportation was recently proposed by Zhao et al [23] and still at the research stage. Recent research indicated that LHPs used in the buildings' hot water systems could achieve the enhanced performance if the solar absorber and heat exchanger are adequately selected and coupled [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Although the volume filling ratio in this study used the previous optimal result, the existence of the pump, condensation liquid storage tank, and evaporation liquid storage tank made the actual evaporation liquid level higher than Zhao et al [25] under the same filling ratio; since the condensation liquid storage tank and evaporation liquid storage tank contribute a big amount of volume; however, those parts had limited contributions on the overall heat transfer.…”
Section: International Journal Of Photoenergymentioning
confidence: 99%
“…According to Zhao et al [25], the loop thermosiphon has the best filling ratio that lies between 30%~50% of the whole volume and has a negative performance when overcharged. …”
Section: Instantaneous Photothermal Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The LHP is a two-phase heat-transfer measure with the working fluid circulating in a loop, thus enabling remote and passive heat transfer at enhanced capacity. Due to its simple operation and environmental effect, LHP has been widely used in the thermal control of satellites and electronics [12][13][14] and it has gradually been gaining attention in the field of solar energy collection and transportation [15][16][17]. The LHP mode is passive, which means it does not consume work.…”
Section: Introductionmentioning
confidence: 99%